The Anatomy of a Multiple Crisis : Why Was Argentina Special and What Can We Learn from It? - Perry, Guillermo; Serven, Luis (World Bank, Washington, DC, 2014)
The Argentine crisis has been variously blamed on fiscal imbalances, real overvaluation, and self-fulfilling investor pessimism triggering a capital flow reversal. The authors provide an encompassing assessment of the role of these and other ingredients in the recent macroeconomic collapse. They show that in the final years of convertibility, Argentina was not hit harder than other emerging markets in Latin America and elsewhere by global terms-of-trade and financial disturbances. So the crisis reflects primarily the high vulnerability to disturbances built into Argentina's policy framework. Three key sources of vulnerability are examined: the hard peg adopted against optimal currency area considerations in a context of wage and price inflexibility; the fragile fiscal position resulting from an expansionary stance in the boom; and the pervasive mismatches in the portfolios of banks' borrowers. While there were important vulnerabilities in each of these areas, neither of them was higher than those affecting other countries in the region, and thus there is not one obvious suspect. But the three reinforced each other in such a perverse way that taken jointly they led to a much larger vulnerability to adverse external shocks than in any other country in the region. Underlying these vulnerabilities was a deep structural problem of the Argentine economy that led to harsh policy dilemmas before and after the crisis erupted. On the one hand, the Argentine trade structure made a peg to the dollar highly inconvenient from the point of view of the real economy. On the other hand, the strong preference of Argentinians for the dollar as a store of value-after the hyperinflation and confiscation experiences of the 1980s-had led to a highly dollarized economy in which a hard peg or even full dollarization seemed reasonable alternatives from a financial point of view.